New Vibrio species associated to molluscan microbiota: a review - Romalde, Jesus L.; Diéguez, Ana L.; Lasa, Aide; Balboa, Sabela (Frontiers in Microbiology, 2014)
The genus Vibrio consists of more than 100 species grouped in 14 clades that are widely distributed in aquatic environments such as estuarine, coastal waters and sediments. A large number of species of this genus are associated with marine organisms like fish, molluscs and crustaceans, in commensal or pathogenic relations. In the last decade, more than 50 new species have been described in the genus Vibrio, due to the introduction of new molecular techniques in bacterial taxonomy, such as multilocus sequence analysis (MLSA) or fluorescent amplified fragment length polymorphism (FAFLP). On the other hand, the increasing number of environmental studies has contributed to improve the knowledge about the family Vibrionaceae and its phylogeny. Vibrio crassostreae, V. breoganii, V. celticus are some of the new Vibrio species described as forming part of the molluscan microbiota. Some of them have been associated with mortalities of different molluscan species, seriously affecting their culture and causing high losses in hatcheries as well as in natural beds. For other species, ecological importance has been demonstrated being highly abundant in different marine habitats and geographical regions. The present work provides an updated overview of the recently characterized Vibrio species isolated from molluscs. In addition, their pathogenic potential and/or environmental importance is discussed.